Distribution of trace elements in edible green seaweed (Caulerpa racemosa) - Mohd Yusuff, Mohd Haikal; Mohamed Rehan, Aisyah; Kamarudin, Kamarul Rahim (2008)
Industrialisation has resulted in large-scale production of anthropogenic pollutants, particularly heavy metals. The process of removal of heavy metals by seaweed, a marine plant species is called biosorption. This helps in improving water quality but might lead to seaweed toxicity as many heavy metals are toxic even in trace amounts. This study aims to analyse the biosorption of metals by edible marine green algae (Caulerpa racemosa). The seaweed species was collected from Sungai Kilim, an area of brackish water near the Langkawi island coastline. Heavy metals analysis was performed by graphite furnace atomic absorption spectrophotometry (GFAAS) to determine the range of heavy metal adsorption. Seaweed samples were treated and prepared with nitric acid 70% and diluted with distilled water (1:1000). Meanwhile, filtered and acidified seawater sample was treated with methyl isobutyl ketone (MIBK) solution followed by 1% ammonium-pyrrolidine dithiocarbonate (APDC) solution. The concentrations of Cu, Fe, Cr and Cd in both the seaweed samples and the seawater samples were determined. The overall concentration was found to range between 0.1μg/L to 7μg/L in Caulerpa racemosa. The results were also compared with the elemental distribution in seawater and with the interim proposed standard for the conservation of marine aquatic recourses. Results showed that concentration of metals in seaweed are higher than seawater due to the persistent biosorption of toxic metal in seaweed. The range was between 0.02μg/L to 0.1μg/L. Further study will be carried out to compare and verify the level of heavy metal elements analysed and to investigate any possible heavy metal contamination in the samples. In future, the data from this study will be compared with the physical analysis of water in Sungai Kilim for the overall analysis of trace metal distribution in C. racemosa.